Community Organizing Strategies in the Implementation of the Community Empowerment Program in Tongauna Village, Konawe Regency - Moita, Sulsalman (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to identify and explain the village community organizing strategy for the implementation of the Community Empowerment Program in Tongauna Village, Tongauna District, Konawe Regency.This study uses a qualitative descriptive approach. Data was collected through in-depth interviews, observations, and document studies, which were then analyzed with a qualitative approach. The results of the study show that the community organizing strategy in the community empowerment program shows: The integration of the community empowerment program, has undergone significant changes in the strengthening of the role of community organizations; The socialization of community empowerment programs results in the involvement of community organizations to identify and plan the most basic community needs; Empowerment program activities involve organizations to build citizen awareness in various development programs; Empowerment program meetings involve community organizations in development planning deliberations; Implementation of empowerment actions, namely the involvement of community organizations in a number of development programs.Evaluation of empowerment programs results in the involvement of community organizations to supervise and evaluate development policies; and the expansion of empowerment programs through the involvement of community organizations to improve the quality of the program, expand the scope of the program and innovate